Self-regulation competences for improving weaker points in geography learning in elementary school - Knez, Sara; Konečnik Kotnik, Eva (Journal for Geography, 2015)
The article is based on the thesis entitled Self-regulated Learning of Geography in Elementary School (Knez 2015) where we examined the situation in the field of self-regulation competencies among 200 primary school pupils attending grades 6–9. Self-regulated learning can improve the weaker points in geography. However, pupils need to have certain self-regulation competences to do so. The research pointed to the incompetence of pupils in many self-regulation areas – the perception of learning geography, self-assessment, seeking help with competent persons, control over learning and using strategies for learning geography.
Keywords: improving weaker points; self-regulation; self-assessment; seeking social assistance; control over learning; strategies for learning geography